2010
DOI: 10.1523/jneurosci.3501-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture of Reward Value Coding in the Human Orbitofrontal Cortex

Abstract: To ensure their survival, animals exhibit a number of reward-directed behaviors, such as foraging for food or searching for mates. This suggests that a core set of brain regions may be shared by many species to process different types of rewards. Conversely, many new brain areas have emerged over the course of evolution, suggesting potential specialization of specific brain regions in the processing of more recent rewards such as money. Here, using functional magnetic resonance imaging in humans, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
263
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(305 citation statements)
references
References 64 publications
(84 reference statements)
34
263
1
7
Order By: Relevance
“…In addition, the OFC was sensitive to visual sex (with effect sizes similar to those in SI), in agreement with the affective valuation often associated with this region (11)(12)(13). Previous models have associated the medial OFC with the monitoring and memory of the reward value of reinforcers (75), and the medial orbital gyrus specifically with the positive value of erotic as opposed to monetary reinforcers (76). In agreement with these findings, we found more activation in the medial OFC for the rewarding visually female condition.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the OFC was sensitive to visual sex (with effect sizes similar to those in SI), in agreement with the affective valuation often associated with this region (11)(12)(13). Previous models have associated the medial OFC with the monitoring and memory of the reward value of reinforcers (75), and the medial orbital gyrus specifically with the positive value of erotic as opposed to monetary reinforcers (76). In agreement with these findings, we found more activation in the medial OFC for the rewarding visually female condition.…”
Section: Discussionsupporting
confidence: 82%
“…Despite its centrality in the representation of values across reward types, the potential specialization of distinct OFC subregions in value representation has become a topic of increasing interest. Consistent with a popular hypothesis proposing the existence of an antero-posterior functional gradient reflecting the abstractness of reinforcers in the OFC (Kringelbach and Rolls, 2004;Kringelbach, 2005), we have recently found a dissociation between experienced values of erotic/monetary rewards and the posterior/anterior OFC (Sescousse et al, 2010(Sescousse et al, , 2013a. This finding is corroborated by recent research (Klein-Flügge et al, 2013;McNamee et al, 2013) and metaanalyses comparing the neural representation of value for different reward modalities (Sescousse et al, 2013b;Clithero and Rangel, 2014).…”
Section: Introductionsupporting
confidence: 90%
“…Here, to investigate how the posterior versus anterior topographic organization of value signals relates to individual morphological variability in the orbitofrontal sulci, we performed subject-by-subject analysis on the data from two previously published fMRI studies using the same experimental protocol, which consistently showed the antero-posterior dissociation between experienced value signals elicited by monetary and erotic rewards in the OFC (Sescousse et al, 2010(Sescousse et al, , 2013a. Our results clearly demonstrate that dissociable experienced value signals for monetary and erotic rewards relate to specific morphological features of the human OFC.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is substantial overlap in the neural systems subserving decision making about different types of rewards , there also appear to be distinctions dependent on reward type Sescousse et al, 2010), indicating that domain-specific as well as more generalized choice networks may be involved in decisions about drugs. Characterizing value-based decision making in problem drug use will likely be key to understanding the pathophysiology of drug use disorders (see Volkow et al, 2010).…”
Section: Introductionmentioning
confidence: 99%